Transient Modelling of Rotating and Stationary Cylindrical Heat Pipes: An Engineering Model - Metin Celik; Geert Paulussen; Dennis van Erp; Wiebren de Jong; Bendiks Jan Boersma (Energies, 2018)
Rotating wickless and stationary capillary cylindrical heat pipes are widely used heat transfer devices. Transient behavior of such heat pipes has been investigated numerically with computational fluid dynamics and lumped parameter models. In this paper, the advantages of both methods are combined into a novel engineering model that is low in computational cost but still accurate and rich in the details it provides. The model describes the interior dynamics of the heat pipe with a 2D representation of a cylindrical heat pipe. Liquid and vapor volumes are coarsely meshed in the axial direction. The cells are allowed to change in size in the radial direction during simulation. This allows for tracking the liquid/vapor interface without having to implement fine meshing. The model includes the equations for mass, momentum and energy and is applicable to both rotating and stationary heat pipes. The predictions of the model are validated with other experimental, numerical, and analytical works having an average deviation of less than 4%. The effects of various parameters on the system are explored. The presented model is suitable for the simulation of heat pipe systems in which both the level of detail and the computational cost are crucial factors.